STRUCTURE. - Smith, Graham (Architects' Journal, 2006)
The article provides an overview of the structural forms of existing buildings surrounding Millennium Square in London, England. The Electric Press building is composed of timber floors and beams with cast-iron columns. The Stansfeld Chambers on the other hand comprise domestic-scale structures. To add diversity to the square, the new theater auditorium is made with steel frame and with concrete and roof-top plantroom.